Konflik Digital, Trauma Komunitas, dan Kebijakan Publik: Analisis Program - Rulinawaty; Lukman Samboteng (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study is to analyze the dynamics of social conflict in Manggarai and assess the suitability of the Reconciliation and Peace Village Program, or Kampung Redam, as a community-based public policy response. This study employed a mixed-methods policy analysis with a predominantly qualitative design. Data were obtained from resident surveys, interviews, monitoring minutes, and program documents. The analysis was conducted using a framework analysis to map the roots of the conflict based on the social-ecological model, conflict transformation, collaborative governance, and policy instrument mix, as well as a simple realist evaluation to understand the relationship between context, policy mechanisms, and expected outcomes. The results indicate that the conflict in Manggarai was formed through the interaction of unemployment, school dropouts, residential density, weak family supervision, youth group solidarity, external provocation, regional stigma, and conflict escalation through social media. Each region exhibited a different configuration of problems. RW 02 was relatively conducive due to strong community coordination, while RW 03, RW 04, RW 05, and RW 012 exhibited a variety of economic, family, security, digital, and psychosocial issues. The most dominant trend in these results is the emergence of a transformation of conflict from physical violence to digital conflict through live broadcasts and the monetization of violent content. The conclusion suggests that Kampung Redam needs to be designed as a context-based, adaptive policy. The implication is that conflict management requires a combination of security instruments, alternative education, trauma recovery, economic empowerment, digital literacy, housing improvements, and cross-sectoral collaborative governance. Keywords: Collaborative Governance, Conflict Transformation, Public Policy, Urban Social Conflict.